2023
DOI: 10.1186/s40104-023-00850-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of the rectum keystone microbiota in modulating the microbial community and growth performance in goat model

Abstract: Background Ruminal microbiota in early life plays critical roles in the life-time health and productivity of ruminant animals. However, understanding of the relationship between gut microbiota and ruminant phenotypes is very limited. Here, the relationship between the rectum microbiota, their primary metabolites, and growth rate of a total of 76 young dairy goats (6-month-old) were analyzed, and then 10 goats with the highest or lowest growth rates respectively were further compared for the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Interestingly, it has been shown that amendment of an obese-associated microbiome with the species Christensenellaceae minuta in mice, can reduce weight gain when subsequently transferred into germ-free mice [ 52 ]. As well, a higher prevalence of Christensenellaceae was found in goats with lower growth rates [ 53 ]. Taken together, the Christensenellaceae R-7 group bacteria may have significant implications modulating body weight of broiler chicken, which may, in turn, explain the reduced performance associated with a high BSFLM content diet.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that amendment of an obese-associated microbiome with the species Christensenellaceae minuta in mice, can reduce weight gain when subsequently transferred into germ-free mice [ 52 ]. As well, a higher prevalence of Christensenellaceae was found in goats with lower growth rates [ 53 ]. Taken together, the Christensenellaceae R-7 group bacteria may have significant implications modulating body weight of broiler chicken, which may, in turn, explain the reduced performance associated with a high BSFLM content diet.…”
Section: Discussionmentioning
confidence: 99%
“…They are capable of producing various essential salts and fatty acids from dietary fiber, thereby playing a significant role in animal growth and development. Moreover, an increase in the abundance of the population of this group has been associated with the mitigation of gastric ulcer pathology (42)(43)(44)(45). The high weighted degree of centrality of this bacterial group in both the control and infected groups indicates its importance in the intestinal tract of both groups of test animals.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated the protective roles of the supplements on gut microbiota dysbiosis in aging mice. At genus levels, norank_f__Muribaculaceae 36) , Lactobacillus 37) , unclassified_f__Lachnospiraceae, norank_f__Lachnospiraceae 38) , Lachnospiraceae_ UCG-006 39) , Alistipes 40) , Streptococcus 41) , Rikenellaceae_ RC9_gut_group 42) , unclassified_f__Prevotellaceae 43) are SCFAs-producing bacteria, which are beneficial for liver health and are reported to be negatively associated with hepatic oxidative stress, inflammation and damage 44) . Norank_f__norank_o__Clostridia_UCG-014 45) , and Pre-votellaceae_UCG-001 46) are beneficial bacteria, that are reported to exert anti-inflammatory function and are inversely correlated with pro-inflammatory cytokines, like IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%